MO060ACUTE KIDNEY INJURY PROMOTES DEVELOPMENT OF A PAPILLARY RENAL CELL ADENOMA-CARCINOMA SEQUENCE FROM RENAL PROGENITORS. (6th June 2020) - Peired, Anna Julie; Allinovi, Marco; Antonelli, Giulia; Angelotti, Maria Lucia; Guzzi, Francesco; Romagnani, Paola
Abstract: Background and Aims: Renal cell carcinoma (RCC) accounts for 2% of all cancers, with about 190, 000 new cases per year worldwide. Risk factors for RCC include obesity, diabetes, hypertension and genetic factors, but the majority of cancers occur in apparent absence of clear risk factors. Acute tissue injury (AKI) causes DNA damage and repair processes involving increased cell mitosis and polyploidization, leading to cell function alterations that may potentially drive cancer development. We proposed to verify whether AKI plays a role in RCC development, and to identify the cellular origin of RCC. Method: We used the following techniques: 1. observational, retrospective clinical trial to identify a possible association of AKI with RCC. 2. Experimental AKI induction in wild-type mice to study tumor development over 36 weeks. 3. Analysis of TCGA Research Network dataset on human papillary RCC (pRCC) molecular characterization, focusing on AKI-driven pathways. 4. Development of mouse models in which the intracellular domain of Notch 1 (NICD1), a molecule modulated during AKI, is expressed constitutively by all Pax8+ tubular epithelial cells (Pax8/NICD1) or only by Pax2+ renal progenitors (Pax2/NICD1) upon induction in adult mice. The mice were sacrificed at 36 weeks or 4 weeks after AKI. 5. Clonal analysis of tumoral lesions with Confetti reporter. 6. Examination of single cell RNA sequencing (RNAseq) data from pRCC patients. Results: We observed that an AKI episode is a major risk factor for pRCC development and recurrence in patients. Wild-type mice subjected to AKI developed pRCC over time in an adenoma-carcinoma sequence, corroborating our human findings. Among AKI-related pathways, Notch1 overexpression in human pRCC associated with worse outcome, prompting us to generate Notch1-overexpressing mice. At 36 weeks o at 4 weeks following AKI, Pax8/NICD1 mice presented a significant decline of renal excretory function as well as type 2 pRCCs. Confetti lineage tracing showed that most of the pRCCs were monoclonal or biclonal, suggesting that they could originate from a local stem cell/progenitor population. Pax2/NICD1 mice presented type 2 pRCCs, and lineage tracing identified single Pax2+ tubular progenitors as the source of pRCCs. Single cell RNAseq analysis confirmed that the molecular signature of the pRCC cell of origin matched the one of human tubular progenitors. Conclusion: This study expose the link between AKI and pRCC development in patients, with important clinical implications. In mice, AKI promotes long-term development of type 2 papillary tumors by activating the AKI-associated Notch1 pathway. Additionally, pRCC originates from clonal proliferation of renal progenitors in a classical adenoma-carcinoma sequence leading to invasive pRCC growth and metastatization in mice.